The Role of Electronic Management in Increasing productivity an Applied study in Hilla Textile Factory (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The  importance of electronic  management has increased  as effective tool to increase productivity in various productive sectors due to development in information technology communication and entry into various fields of life therefore we will clarify the need for the role of electronic management in the productive sectors because productive companies are productive affected by the external environment  the research contained the original and sun-question and three hypotheses to prove it in the research and its relationship to increasing productivity at the Hilla textile factory is the use of the curriculum descriptive analytical to prove hypothesis to achieve the objectives of the researcher designed a questionnaire form for the employees of the lab workers. They were randomly selected. The questionnaire included 32 items to collect the initial information from the sample of 340 employees out of the total sample size of 1425 employees and the testing of hypotheses using the statistical methods of social sciences SPSS has been used many statistical methods to achieve the objectives of the study, including coefficient of stability using the Alpha-Karnobakh coefficient of the terms of resolution, frequencies, percentages and averages and standard deviations and analysis ascertain the hypotheses of the study and the study reached. There is statistically significant effect of the electronic management on the variable the lack of specialized cadres in production to increase productivity at the level of significance of. α ≤ 0.05. There is statistically significant effect of the electronic management on the variable the role of senior management in the application of development processes when increasing the output at the level of significance of. α ≤ 0.05 . There is a statistically significant effect of the electronic management on the variable Satisfaction of employees with the level of services of significance of α ≤ 0.05.